(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 1996)
The purpose of this article is to solve the apparent conflict between the Arbitration Law (Lei de Arbitragem - Lei n. 9,307/96) that allows the arbitration clause in the standard contracts and the Consumer's Rights Code (Código de Defesa do Consumidor - Lei n. 8.078/90) that considers abusive such clause in its art. 51. VII. For better understanding of the question, this article tries to establish each law under its specific circunstance, defending the idea we are in the 4th phase of the modern law, characterized by complexity - wich implies maintenance of the former phases instead of substituing one by another. Therefore, it can be infered that both laws are in force, each one in its own field.